Research of dispersity and chemical composition of particles in the combustion products at gas-peat mixture burning in the steam boilerBKZ-210-140F - V. A. Kuzmin; I. A. Zagray; I. A. Desyatkov (Известия высших учебных заведений: Проблемы энергетики, 2017)
Dispersivity and chemical composition of ash and slag particles at dust combustion of milled peat were investigated in this work. Shapes and sizes of the particles depending on the sampling points in different parts of the boiler system were determined experimentally. The histograms and the particle size distribution functions were obtained.